КӨРКЕМЛИК БИЛИМЛЕНДИРИЎ СИСТЕМАСЫНДА ТАЛАБАЛАРДЫҢ КӨРКЕМ ДӨРЕТИЎШИЛИК УҚЫПЛЫЛЫҒЫН РАЎАЖЛАНДЫРЫЎ МӘСЕЛЕЛЕРИ - Уразимова, Т.В. (ILIM hám JÁMIYET, 2021)
The article deals with issues of art education, developing artistic-creative abilities of student, since that nowadays in society arose attention to the problems of art education. Aesthetic education plays the great role in activating world-view, intellectual and creative potential of human-being. So that in teaching process we should focus our attention on creating appropriate conditions for instructing creative people, where we are ready to communicate, collaborate.